2016
DOI: 10.1016/j.jacc.2015.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Mechanisms Underlying the Functional Benefits of a Myocardial Matrix Hydrogel for Post-MI Treatment

Abstract: BACKGROUND There is increasing need for better therapies to prevent the development of heart failure after myocardial infarction (MI). An injectable hydrogel derived from decellularized porcine ventricular myocardium has been shown to halt the post-infarction progression of negative left ventricular remodeling and decline in cardiac function in both small and large animal models. OBJECTIVES We sought to elucidate the tissue level mechanisms underlying the therapeutic benefits of myocardial matrix injection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 42 publications
5
117
0
Order By: Relevance
“…Our photo-crosslinked chitosan hydrogel was degradable by lysozyme as confirmed in previous studies (41,42). Furthermore, prior studies have shown that PEG-based hydrogels have tunable degradation rates and are well tolerated (66,67), and the use of DMSO in our E2/ND/G platform was shown to have no biological effects or adverse toxicities. We used methacrylated glycol chitosan G, which enabled local delivery of E2/ND in a minimally invasive manner using blue-light assisted gelification.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our photo-crosslinked chitosan hydrogel was degradable by lysozyme as confirmed in previous studies (41,42). Furthermore, prior studies have shown that PEG-based hydrogels have tunable degradation rates and are well tolerated (66,67), and the use of DMSO in our E2/ND/G platform was shown to have no biological effects or adverse toxicities. We used methacrylated glycol chitosan G, which enabled local delivery of E2/ND in a minimally invasive manner using blue-light assisted gelification.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, ND safety and biocompatibility have been recently demonstrated in a nonhuman primate study involving systemic administration of NDs to both genders, where no apparent toxicity or impaired organ function was observed (64). Similarly, the safety and biocompatibility of hydrogels allow for their versatile applications in tissue engineering (36)(37)(38)66). Our photo-crosslinked chitosan hydrogel was degradable by lysozyme as confirmed in previous studies (41,42).…”
Section: Discussionsupporting
confidence: 80%
“…While injectability may be related to the viscoelastic properties (ECM pre-gel viscosity and gelation time), injectability has been independently confirmed in vitro and/or in vivo for heart [55, 60, 7481], spinal cord [82], small intestine [26, 51], umbilical cord [63], skeletal muscle [63, 64, 83], tendon [59, 84], dermal [23], lung [49], liver [57], cartilage [70], urinary bladder [21, 22, 24, 82] and adipose [50, 67] ECM hydrogels with reported 18–27 gauge syringes or catheters. For example, porcine myocardial gel (6 mg/mL) was confirmed to be injectable through a 27 gauge catheter [75] , and then confirmed to be injectable via NOGA guided MyoSTAR catheter (27 gauge), which is the current gold standard delivery device used in cellular cardiomyoplasty procedures [75].…”
Section: Ecm Hydrogel Characterizationmentioning
confidence: 99%
“…Cardiac scafold is a therapeutic intervention with low cost and eicacy and has signiicantly improved patients' quality of life and prolonged their longevity [71][72][73][74]. The scafold must reduce local micro-environment hostility persist for a suicient time period over injured area to facilitate native cell migration and integration with native tissue to be feasible for cardiac repair/remodelling.…”
Section: Tissue Regeneration: a Biomimetic Designmentioning
confidence: 99%
“…This model of study therefore provides an opportunity to interrogate the molecular and cellular mechanism governing regeneration of immature human heart tissue [73,77].…”
Section: Efect Of Acellular Scafold On Ventricular Function and Cardimentioning
confidence: 99%